Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 8- Survey of adult behaviour of Spissipes Section species of Culex (Melanoconion) in South-Eastern Brazil - Oswaldo Paulo Forattini; Maria Anice Mureb Sallum; Iná Kakitani; Eduardo Massad; Daniel Marucci (Universidade de São Paulo, 1995)
A study of Spissipes Section of Culex (Melanoconion) adults behaviour was carried out from August 1992 through December 1993 in human dominated (anthropic) environment in the Ribeira Valley, S.Paulo State, Brazil. By sampling at several sites it the dominance of Culex ribeirensis and Cx. sacchettae became evident even through a total number of ten species was recorded. Those two mosquitoes showed a clear tendency to frequent the domiciliary environment where they were caught, both indoor and outdoor, through the use of the human bait. In the outside environments, the residual patchy forests seems to display a concentration role, from which these adults spread to the open land and reach the dwellings. As their vector competence has been demonstrated through the virus isolations in natural conditions, it is advisable to pay attention to the presence of these mosquitoes in the man-made environment.